2021
DOI: 10.1080/02656736.2021.1947529
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of liver stiffness measurement in patients with hepatocellular carcinoma (HCC) treated by radiofrequency ablation: a meta-analysis

Abstract: Background: In patients with stage 0-A (as per Milan criteria) hepatocellular carcinoma (HCC) imageguided ablation is less invasive and requires shorter hospitalization than resection, but long-term prognosis is poorer. This meta-analysis was conducted to investigate whether liver stiffness measurement (LSM) could be used to predict prognosis in HCC patients after tumor ablation. Methods: A literature search was conducted for all studies published till July 2020 in PubMed, Web of Science, Cochrane Library and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Changes in ECM composition are one of the characterizing features of the TME and it is widely accepted that this actively contributes to disease progression in different tumors 20,21 . This significance of altered ECM is seen in HCC patients, where increases in liver stiffness are associated with hepatic dysfunction, poor prognosis, and survival [22][23][24] . Recent studies have even shown that increased liver stiffness is a predictor for mortality and need for mechanical ventilation among patients hospitalized with COVID-19 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ECM composition are one of the characterizing features of the TME and it is widely accepted that this actively contributes to disease progression in different tumors 20,21 . This significance of altered ECM is seen in HCC patients, where increases in liver stiffness are associated with hepatic dysfunction, poor prognosis, and survival [22][23][24] . Recent studies have even shown that increased liver stiffness is a predictor for mortality and need for mechanical ventilation among patients hospitalized with COVID-19 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Transaminases, albumin, and prothrombin time were closely related to the degree of liver inflammation, while liver stiffness was associated with liver fibrosis, inflammation, and portal pressure. Therefore, the inflammatory state of the liver and the pressure of the portal vein could affect LSM measurements, thus, it may affect the accuracy of liver fibrosis assessment [ 30 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that ARFI imaging is a useful tool for assessing liver functional reserve. As another example, a recent meta-analysis reported that ARFI scores may be a good predictor of HCC recurrence-free survival in patients receiving radiofrequency ablation[ 24 ]. In a series of 1808 patients who received ARFI, those patients with an ARFI score > 1.33 cm/s showed a higher probability of HCC development than those with an ARFI score ≤ 1.33 cm/s[ 25 ].…”
Section: Discussionmentioning
confidence: 99%